Preparation and Identification of some derivatives of 1,3-oxazepene ring derivatives from 3,4-diamino toluene and studying their bacterial activity - Khamaael. M.F. (Tikrit Journal of Pure Science, 2023)
This search includes preparation Schiff Bases (O1-5) from the reaction between 3,4-Diamino toluene with different aromatic aldehyde without using a solvents, by thermal fusion. preparation the compounds of,  1,3 - oxazepen 4,7- Dione (O6-10) by ring closer reaction through the reaction of the derivatives Schiff (O1-5) with maleic anhydride , The prepared compounds were confirmed by infrared (I.R), Nuclear Magnetic resonance spectroscopy (1H-NMR), as the physical methods such color and melting point, the biological activity was studied against of bacteria.